2009
DOI: 10.1126/science.1167342
|View full text |Cite
|
Sign up to set email alerts
|

Human Substantia Nigra Neurons Encode Unexpected Financial Rewards

Abstract: Human Substantia Nigra Neurons Encode www.sciencemag.org (this information is current as of August 6, 2009 ):The following resources related to this article are available online at http://www.sciencemag.org/cgi/content/full/sci;325/5939/393-c A correction has been published for this article at:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
176
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(196 citation statements)
references
References 26 publications
14
176
4
Order By: Relevance
“…Many studies have confirmed, quantified, and extended reward prediction error coding by dopamine neurons, even in humans (Zaghloul et al, 2009). The dopamine neurons of monkeys that have not learned to predict reward show continued positive and negative prediction errors at the time of reward or reward omission, respectively.…”
Section: Phasic Dopamine Signals Represent Model-free Prediction Errorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Many studies have confirmed, quantified, and extended reward prediction error coding by dopamine neurons, even in humans (Zaghloul et al, 2009). The dopamine neurons of monkeys that have not learned to predict reward show continued positive and negative prediction errors at the time of reward or reward omission, respectively.…”
Section: Phasic Dopamine Signals Represent Model-free Prediction Errorsmentioning
confidence: 96%
“…In humans, functional MRI (fMRI) studies and even in vivo surgical recordings (Zaghloul et al, 2009) have reported correlates of prediction-error signals in the striatum that resemble those of dopamine neurons recorded in animals, including phasic (event-related) positive and negative prediction error responses (McClure et al, 2003a;O'Doherty et al, 2003;D'Ardenne et al, 2008) that reflect probability (e.g. Abler et al 2006;Burke et al 2010;Spicer et al 2007;Tobler et al 2007) and more specific predictions of formal learning theories Kahnt et al, 2012;Rutledge et al, 2010;Tobler et al, 2007).…”
Section: Phasic Dopamine Signals Represent Model-free Prediction Errorsmentioning
confidence: 99%
“…52 Recent experiments have provided fascinating evidence of the link between utility and chemical processes in the brain. See, for example, Zaghloul, Blanco, Weidemann, McGill, Jaggi, Baltuch and Kahana [168]. 53 Attention was drawn to this phenomenon by Brickman, Coates and Janoff-Bulman's [18] study of lottery winners and paraplegics, and has become the subject of a large literature.…”
Section: Adaptive Utility and Relative Consumptionmentioning
confidence: 99%
“…Across a range of species from rats to humans, dopamine cells burst fire in response to positive 'prediction errors' (events that are better than expected), whereas these same cells pause in response to negative prediction errors (events that are worse than expected) (Schultz et al, 1997;Bayer and Glimcher, 2005;Roesch et al, 2007;Joshua et al, 2006;Pan et al, 2008;Zaghloul et al, 2009). A key assumption of reinforcement learning models is that these bursts and dips act as a 'teaching signal' by modifying synaptic plasticity in target structures Wickens et al, 2003;Frank, 2005).…”
Section: Dissociating Corticostriatal Genetic Components To Learningmentioning
confidence: 99%